TPQ Inklusif: Integrasi beyond the Rukhsah dan strength based approach dalam pendidikan keagamaan penyandang disabilitas - Kemal Pasha Wijaya Wijaya; Juy Zulfi Ali Ali Akbar; Muhammad Wahyudi Azzukhruf (Literal: Disability Studies Journal, 2026)
Religious education is a fundamental right for every individual, including persons with disabilities. However, access to inclusive religious education, particularly within Islamic Structured Afternoon Schools—known as Taman Pendidikan Al-Qur’an (TPQ)—has not yet provided the necessary support to ensure equal rights in religious schooling for persons with disabilities. This study aims to construct a conceptual model for an Inclusive TPQ by integrating the Beyond the Rukhsah approach and the Strength-Based Approach to support equal access to religious education. This study employs a qualitative, library research approach with a theory synthesis conceptual design. The analysis was conducted by identifying the phenomenon and subsequently integrating the two theories as a conceptual framework. The results of the study indicate that the Beyond the Rukhsah approach plays a crucial role in building a religious paradigm that positions persons with disabilities as equal subjects, while the Strength-Based Approach emphasizes learning based on individual potential. The integration of these two approaches yields an Inclusive TPQ model that encompasses adaptive and participatory aspects of lesson planning, implementation, and evaluation. This model not only expands access to religious education but also supports the strengthening of religious character and the equal social participation of persons with disabilities. Thus, the Inclusive TPQ has the potential to serve as an alternative solution for realizing fair, inclusive, and sustainable religious education